Local Wisdom Pesantren sebagai Core Value Pengembangan Budaya Organisasi Kelembagaan Pendidikan Islam - Fauzi, Ahmad (Proceedings of Annual Conference for Muslim Scholars, 2019)
At the practical level, pesantren as an organization (noble industry), has significantly colored today's social reality. Therefore, the existence of pesantren continues to play its role dynamically and provides various contributions. This view cannot be separated from the culture and scientific traditions of pesantren which are coherently preserved. The dynamics of pesantren institutional development, its essence cannot be separated from the value system, and become core beliefs and core values in the life of pesantren, including in the management and development of pesantren educational organization culture. Internalization of these values is part of the kiai's construction of his understanding of the Qur'an and al-Hadith. In this context, the value system built by the kiai as the foundation of the pesantren institution is better known as the term (satlogi santri and trilogy of santri, panca santri awareness). Internalization of pesantren values is understood as local wisdom and is the basis for developing the Islamic education system. The construction of these values is expected to give birth to positive energy and significantly be able to influence the behavior and social actions of individuals in realizing the culture of Islamic education organizations that are more effective (effective school). Therefore the practical implications of this study aim to build the culture of Islamic education organizations based on the pesantren social value system, besides that as (shifting paradigm). The construction of the above social values is expected to increase productivity performance and become (the main controller and mindset) of the entire organizational culture, towards organizations that are oriented towards (tend to religious and moral values) and the creation of effective Islamic education (effective schools).